A preparation method of PHA-PPTA copolymerized fibrid and PBO-PPTA fibrid
By introducing PHA-PPTA and PBO-PPTA copolymerized precipitation fibers into PBO fibers, combined with high negative pressure thermal cyclization technology, the problem of poor dissolution ability of PBO fibers in conventional solvents is solved, and the preparation of high specific surface area fibers is achieved and The optimization of performance has promoted the industrial application of PBO paper-based materials.
Patent Information
- Application Number
- CN202310391961.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-04-13
AI Technical Summary
The development of PBO high-performance fiber paper-based materials in the prior art is limited by the problem of raw materials, especially the poor dissolution ability of PBO precipitated fibers in conventional solvents, resulting in low production efficiency and a lot of waste acid wastewater, making it difficult to achieve industrial production.
The preparation method of PHA-PPTA copolymerized precipitation fiber and PBO-PPTA precipitation fiber is prepared by in-situ copolymerization and high-speed shearing and other technical means, and the fibers are realized by combining high negative pressure thermal cyclization technology. efficient preparation.
This method not only retains the excellent properties of PBO fibers with high strength, high modulus, high temperature resistance and weak moisture absorption, but also improves the liquid phase dispersion performance and compound enhancement effect by introducing PPTA aramid, and can be used to prepare paper with excellent performance Base insulation material.
Smart Images

Figure CN116427050B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new material preparation, and in particular to a preparation method of PHA-PPTA copolymerized fibrid and PBO-PPTA fibrid. Background Art
[0002] Polybenzobisoxazole (PBO) fiber is a high-performance aromatic heterocyclic fiber with the characteristics of high strength, high modulus, high temperature resistance and high flame retardancy. Its unique and excellent performance mainly comes from the particularity of its molecular structure. Its molecular structure is a rigid rod-shaped polymer with a crystalline structure of skin-core structure. The core layer is composed of microfibers under the smooth skin. The microfibers are composed of PBO molecules with high orientation along the longitudinal axis of the fiber, which makes PBO fiber perform better than other fibers under high temperature and harsh environment. The breaking strength of PBO fiber reaches 37cn / dtex, and its elastic modulus reaches 280Gpa, which is twice that of aramid. The thermal decomposition temperature reaches 650℃, and it can be used for a long time under 300-350℃. It is currently the most temperature-resistant organic fiber material, with a limiting oxygen index (LOI) of 68%, excellent flame retardancy, almost no toxic gas is generated during combustion, and it has a low dielectric constant (2.6-3.0) and dielectric loss. It is known as the super fiber of the 21st century.
[0003] Compared with aramid fiber materials, its dielectric properties and high temperature resistance are better, and its moisture absorption rate is much lower. At present, most of the paper-based materials widely used in aviation, aerospace, shipbuilding and other industries are made of aramid fibers. Compared with the most representative aramid paper in the prior art, the long-term use temperature of PBO special paper is higher than 300°C. At the same time, it also has the characteristics of high strength, high insulation, low dielectric, corrosion resistance and low water absorption, which greatly improves the use temperature of high-temperature insulation paper in the prior art, and overcomes the problems of reduced insulation strength, increased dielectric loss and weakened electromagnetic wave transmission performance caused by the high water absorption rate of aramid paper. An important factor restricting the development of PBO high-performance fiber paper-based materials is the raw material problem. In the preparation process, PBO short-cut fibers and PBO precipitated fibers (or PBO pulp) need to be prepared as raw materials. Among them, PBO precipitated fibers need to have a large specific surface area to play the role of filling and bonding between fibers.
[0004] Because PBO fiber has very poor solubility in conventional solvents and can only be dissolved in a small amount of solvents such as concentrated sulfuric acid, methanesulfonic acid, and polyphosphoric acid, on the one hand, the production efficiency is low and it is difficult to achieve a high specific surface area. On the other hand, a large amount of waste acid and wastewater will be generated, making it difficult to achieve industrial production, which seriously limits the development of PBO paper-based materials. A large number of researchers have carried out technical research, such as the reference literature: Research on the fibrillation method of PBO fiber. Huang Youhe, Synthetic Fiber Industry, 2005. 28 (5): Huang Youhe et al. used chemical and physical methods to modify the surface of PBO fiber to achieve the fibrillation of PBO fiber; Preparation of PBO fiber precipitation pulp for papermaking. Wang Xiwen, China Papermaking, 2007. 26 (5): Wang Xiwen directly dissolved PBO fiber in 98% concentrated sulfuric acid and prepared PBO pulp for papermaking by precipitation method; Research on PBO fibrillation. Wang Yi and Wang Xiwen, Synthetic Fiber Industry, 2010. 33 (6): PBO pulp with large aspect ratio, high specific surface area and a large number of fibrillated structures was prepared by mechanical treatment. In addition, the invention patent with publication number CN113882185 A discloses a method for preparing PBO precipitation fibrils for pulp, which prepares PBO precipitation fibril pulp by polyhydroxyamide (PHA) precursor. Although the above methods have improved the above problems and prepared PBO fibrids with high specific surface area, PBO polymer has a highly symmetrical chemical structure and PBO fibrids are extremely inert. Therefore, the composite reinforcement effect of PBO fibrid pulp is far lower than that of fibrids prepared from aramid. Summary of the invention
[0005] The present invention aims to solve the defects of single product performance in the prior art and the product needs on the market now, and provides a preparation method of PHA-PPTA copolymer fibrid and PBO-PPTA fibrid. The present invention combines the advantages and disadvantages of PBO fibrid and aramid fiber, designs a special ratio, starts from the polymer molecular structure level, adopts an in-situ copolymerization method to prepare a precursor PHA-PPTA stock solution, prepares PHA-PPTA copolymer fibrid with high specific surface area by high-speed shearing, and then obtains PBO-PPTA copolymer fibrid with high specific surface area by high negative pressure thermal cyclization. It not only retains the excellent properties of PBO fibrid such as high strength, high modulus, high temperature resistance, and weak moisture absorption, but also improves the liquid phase dispersion performance and composite reinforcement effect of PBO fibrid by introducing PPTA aramid (para-aramid molecule fragment) with strong polar amide groups, so that it can become a paper-based insulation material with excellent performance, so as to realize the promotion and application of PBO paper-based materials in more fields.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A method for preparing PHA-PPTA copolymerized fibrid comprises the following steps:
[0008] Step 1: Prepare the precursor PHA-PPTA polymer solution:
[0009] Using 4,6-diaminoresorcinol hydrochloride as the first reaction monomer and terephthaloyl chloride as the second reaction monomer, under nitrogen protection, adding a certain amount of aprotic polar solvent, adding an antioxidant stannous chloride, adding the first reaction monomer 4,6-diaminoresorcinol hydrochloride, adding a catalyst and the second reaction monomer terephthaloyl chloride at one time under stirring, controlling the temperature at 0-35° C. to react for 10-30 hours, thereby preparing a prepolymer solution A;
[0010] With p-phenylenediamine as the third reaction monomer and terephthaloyl chloride as the fourth reaction monomer, under nitrogen protection, add a certain amount of aprotic polar solvent, add dissolving salt lithium chloride, add the third reaction monomer p-phenylenediamine, stir to dissolve, add the fourth reaction monomer terephthaloyl chloride at one time under stirring, control the temperature at 0-30°C to react for 10-30h, and obtain a prepolymer solution B;
[0011] Add prepolymer solution A and prepolymer solution B into a polymerization kettle, control the temperature at 0-5°C, stir and mix for 30 minutes, then raise the temperature to 20-80°C and continue the reaction for 5-20 hours to obtain a precursor PHA-PPTA polymer solution;
[0012] Step 2: The precursor PHA-PPTA polymer solution obtained in step 1 is neutralized with an organic amine, diluted to a mass concentration of 1-5%, mixed and degassed, and then the treated solution is injected into a stirred and temperature-controlled precipitate, and under stirring, it is rapidly dispersed into an ultra-thin flocculent PHA-PPTA precipitated fiber suspension with a dendritic structure; the suspension is filtered, washed, and dried to obtain PHA-PPTA copolymerized precipitated fibers.
[0013] Preferably, the non-protonic polar solvent in step one is one or more of N-methylpyrrolidone, dimethylformamide, and N,N-dimethylacetamide. In preparing prepolymer solution A, the molar concentration of the first reaction monomer 4,6-diaminoresorcinol hydrochloride is preferably 0.1 mol / L to 1 mol / L; in preparing prepolymer solution B, the molar concentration of the third reaction monomer p-phenylenediamine is preferably 0.1 mol / L to 1 mol / L.
[0014] Preferably, in step 1, the total molar amount of the first reaction monomer and the third reaction monomer added to the total molar amount of the second reaction monomer and the fourth reaction monomer added is 1:0.8-1.0; wherein the molar ratio of the first reaction monomer to the third reaction monomer is 8-2:2-8.
[0015] Preferably, in the step 1, the mass of the antioxidant stannous chloride added is 0.1-3 wt % of 4,6-diaminoresorcinol hydrochloride; when preparing the prepolymer solution B, the mass of the dissolving salt lithium chloride added is 3-8% of the organic solvent.
[0016] Preferably, the catalyst in step 1 is at least one of pyridine, triethylamine or isoquinoline, and the mass of the catalyst is 0.5-6 wt % of the mass of 4,6-diaminoresorcinol hydrochloride.
[0017] Preferably, the stirring speed of the stirring in step 2 is 1000-9000 rpm, and the injection conditions include: the temperature is 15-60°C.
[0018] Preferably, the precipitate in step 2 is at least one or more of DMAC, NMP, water, methanol, ethanol and acetone.
[0019] Preferably, in the step 2, the volume ratio of the diluted precursor PHA-PPTA dilution liquid to the precipitate liquid is 1:15.
[0020] A method for preparing PBO-PPTA fibrids comprises the steps of subjecting PHA-PPTA copolymerized fibrids to high temperature thermal cyclization under vacuum conditions to prepare PBO-PPTA fibrids.
[0021] Preferably, the conditions for the thermal cyclization include: vacuum condition of -0.05 MPa to -0.09 MPa, temperature of 300-480° C., and time of 5-40 min.
[0022] The beneficial effects of this technical solution are as follows:
[0023] 1. The present invention provides a method for preparing a PHA-PPTA copolymer fibrid, which adopts a polymerization method of prepolymerizing two polymer segments and then post-polymerizing them. The proportion of molecular segments is controlled by the design of the ratio to adjust the specific performance products according to the application scenarios of the fibrid. The fiber has a strong surface force because it contains a large number of unclosed hydroxyl groups (-OH) and amide bonds in its chemical structure, so it has a strong solubility in common polar solvents such as DMAC and NMP. By adjusting the concentration, viscosity and rotation speed of the PHA-PPTA polymer solution, the morphological structure and specific surface area of the PHA-PPTA copolymer fibrid can be optimized and controlled. The prepared PHA-PPTA copolymer fibrid is ultra-thin and fluffy, has a good high specific surface area, and is very beneficial for use as pulp fiber to prepare paper-based materials.
[0024] 2. The present invention provides a method for preparing PHA-PPTA copolymerized fibrils, in which PHA-PPTA copolymerized fibrils are prepared by neutralizing, filtering, degassing, diluting and other treatments of a PHA-PPTA polymerization stock solution. Because the polymerization reaction solvent is a common polar solvent such as DMAC and NMP, and the precipitate is at least one or more of DMAC, NMP, water, methanol, ethanol and acetone, the process is simple and the solvent is easy to separate and recycle, so the method has strong operability, less wastewater and low cost, and is a new method for preparing PHA-PPTA copolymerized fibrils in a green way.
[0025] 3. The present invention provides a method for preparing PBO-PPTA fibrids, which is prepared by direct thermal cyclization of PHA-PPTA copolymerized fibrids, retaining the excellent properties of PBO such as high temperature resistance and weak moisture absorption, and preparing fibers with high specific surface area. By introducing PPTA with amide bonds, it has the liquid phase dispersion performance and composite reinforcement effect of aramid fibrids. It can be used as pulp fiber to prepare PBO paper-based materials, or as a high-efficiency filler to prepare other polymer-based composite materials to improve the high temperature resistance and mechanical properties of polymer-based composite materials.
[0026] 4. The preparation method of PHA-PPTA copolymer precipitated fibers and PBO-PPTA precipitated fibers provided by the present invention can realize the mass production of PHA-PPTA copolymer precipitated fibers and PBO-PPTA precipitated fibers, which is beneficial to fill the deficiencies of polyimide, aramid and other paper-based materials in high temperature resistance, mechanical strength and insulation performance, meet the use requirements of high-temperature insulating paper with higher temperature, higher strength and higher insulation in harsh application occasions, and meet the use requirements of paper-based materials with low water absorption, low dielectric constant, low dielectric loss and high wave transmission performance in the aerospace field.
[0027] 5. The present invention provides a method for preparing a PHA-PPTA copolymer fibrid, which adopts a polymerization method of prepolymerizing two polymer segments and then post-polymerizing them, and controls the proportion of molecular segments by designing the ratio to adjust the specific performance products according to the application scenarios of the fibrid. The fiber has a strong surface force because it contains a large number of unclosed hydroxyl groups (-OH) and amide bonds in its chemical structure. The prepared PHA-MPIA fibrid is ultra-thin and fluffy, and has a good high specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0030] Detection methods of the precipitated fibers in Examples 1 to 5 and Comparative Examples 1 to 5: fiber length (average length calculated by optical microscope test), specific surface area (tested by specific surface area tester), thermal decomposition temperature (thermogravimetric analyzer).
[0031] Example 1
[0032] A method for preparing PHA-PPTA fibrids comprises the following steps:
[0033] Step 1:
[0034] In a 2L polymerization tank, add 600 ml of N,N-dimethylacetamide, pass nitrogen, add 30.00 g of 4,6-diaminoresorcinol hydrochloride, add 0.03 g of antioxidant stannous chloride, stir and react for 30 min, add 30.87 g of terephthaloyl chloride, stir for 30 min, add 0.75 g of catalyst isoquinoline, control the temperature at 20°C and stir and react for 24 h to obtain prepolymer solution A.
[0035] In a 2L polymerization tank, add 600ml of N,N-dimethylacetamide, pass nitrogen, add 30.00g of lithium chloride as a dissolving salt, and completely dissolve it under stirring at 80℃, then lower the system temperature to 5℃ (the purpose of heating first and then cooling is to facilitate the rapid dissolution of lithium chloride, and the purpose of cooling is to prevent the deterioration of p-phenylenediamine at a higher temperature and affect the polymerization degree), add 15.22g of p-phenylenediamine, and after it is completely dissolved, add 24.74g of terephthaloyl chloride, control the temperature at 5℃ and stir the reaction for 15h to obtain a prepolymerization solution B.
[0036] Then, the prepolymerization solution A and the prepolymerization solution B were added into a 4L polymerization tank, the temperature was controlled at 0°C and the mixture was stirred at high speed for 30 minutes, and then the temperature was raised to 30°C and the reaction was continued for 15 hours to obtain the precursor PHA-PPTA polymer solution.
[0037] Step 2:
[0038] The precursor PHA-PPTA polymer solution obtained in step 1 is added with diethylamine to neutralize the hydrochloric acid in the solution system, filtered, diluted to a diluent with a mass concentration of 1%, mixed and degassed (after mixing in a polymerization kettle, the solution is slowly stirred and degassed at 60°C for 5 hours under a vacuum degree of -0.08Mpa), and then the treated solution is injected into the stirred and temperature-controlled DMAC precipitate, the stirring speed of which is 5000 rpm, and the injection conditions include: the temperature is 20°C; the volume ratio of the diluted precursor PHA-PPTA dilution solution to the precipitate is 1:15; under the action of high-speed stirring, the solution is rapidly dispersed into an ultra-thin flocculent PHA-PPTA precipitated fiber suspension with a dendritic structure; the suspension is filtered, washed (washed with desalted water), and dried (placed in a vacuum drying oven for drying, the drying conditions are: vacuum degree: -0.09Mpa, temperature: 120°C, time 3h), to obtain PHA-PPTA copolymerized precipitated fibers.
[0039] A method for preparing PBO-PPTA fibrids, wherein PHA-PPTA copolymerized fibrids are subjected to high-temperature cyclization to obtain PBO-PPTA fibrids with a high specific surface area, wherein the conditions for the thermal cyclization include: a vacuum degree of -0.09 Mpa, a temperature of 450°C, and a time of 10 minutes.
[0040] The PBO fibrillated pulp prepared by the above method has an average length of 1.4 mm and a specific surface area of 30 m 2 / g.
[0041] Example 2
[0042] A method for preparing PHA-PPTA fibrids comprises the following steps:
[0043] Step 1:
[0044] In a 2L polymerization tank, add 600 ml of N,N-dimethylacetamide, pass nitrogen, add 30.00 g of 4,6-diaminoresorcinol hydrochloride, add 0.03 g of antioxidant stannous chloride, stir and react for 30 min, add 30.87 g of terephthaloyl chloride, stir for 30 min, add 0.75 g of catalyst isoquinoline, control the temperature at 20°C and stir and react for 24 h to obtain prepolymer solution A.
[0045] In a 2L polymerization tank, add 600ml of N,N-dimethylacetamide, pass nitrogen, add 20.00g of lithium chloride as a dissolving salt, and completely dissolve it under stirring at 80°C. Then lower the system temperature to 5°C, add 10.15g of p-phenylenediamine, and after it is completely dissolved, add 15.38g of terephthaloyl chloride, control the temperature at 5°C, stir and react for 15h, and obtain a prepolymer solution B.
[0046] Then, the prepolymerization solution A and the prepolymerization solution B were added into a 4L polymerization tank, the temperature was controlled at 0°C and the mixture was stirred at high speed for 30 minutes, and then the temperature was raised to 30°C and the reaction was continued for 15 hours to obtain the precursor PHA-PPTA polymer solution.
[0047] Step 2:
[0048] The precursor PHA-PPTA polymer solution obtained in step 1 is added with diethylamine to neutralize the hydrochloric acid in the solution system, filtered, diluted to a diluent with a mass concentration of 1%, mixed and degassed (after mixing in a polymerization kettle, the solution is slowly stirred and degassed at 60°C for 5 hours under a vacuum degree of -0.08Mpa), and then the treated solution is injected into the stirred and temperature-controlled DMAC precipitate, the stirring speed of which is 5000 rpm, and the injection conditions include: the temperature is 20°C; the volume ratio of the diluted precursor PHA-PPTA dilution solution to the precipitate is 1:15; under the action of high-speed stirring, the solution is rapidly dispersed into an ultra-thin flocculent PHA-PPTA precipitated fiber suspension with a dendritic structure; the suspension is filtered, washed (washed with desalted water), and dried (placed in a vacuum drying oven for drying, the drying conditions are: vacuum degree: -0.09Mpa, temperature: 120°C, time 3h), to obtain PHA-PPTA copolymerized precipitated fibers.
[0049] A method for preparing PBO-PPTA fibrids, wherein PHA-PPTA copolymerized fibrids are subjected to high-temperature cyclization to obtain PBO-PPTA fibrids with a high specific surface area, wherein the conditions for the thermal cyclization include: a vacuum degree of -0.09 Mpa, a temperature of 450°C, and a time of 10 minutes.
[0050] The PBO fibrillated pulp prepared by the above method has an average length of 1.9 mm and a specific surface area of 36 m 2 / g.
[0051] Example 3
[0052] A method for preparing PHA-PPTA fibrids comprises the following steps:
[0053] Step 1:
[0054] In a 2L polymerization tank, add 600 ml of N,N-dimethylacetamide, pass nitrogen, add 40.00 g of 4,6-diaminoresorcinol hydrochloride, add 0.04 g of antioxidant stannous chloride, stir and react for 30 min, add 41.16 g of terephthaloyl chloride, stir for 30 min, add 1.05 g of catalyst isoquinoline, control the temperature at 20°C and stir and react for 26 h to obtain prepolymer solution A.
[0055] In a 2L polymerization tank, add 300ml of N,N-dimethylacetamide, pass nitrogen, add 13.50g of lithium chloride as a dissolving salt, and completely dissolve it under stirring at 80°C. Then lower the system temperature to 5°C, add 8.70g of p-phenylenediamine, and after it is completely dissolved, add 11.75g of terephthaloyl chloride, control the temperature at 5°C, stir and react for 15h, and obtain a prepolymer solution B.
[0056] Then, the prepolymerization solution A and the prepolymerization solution B were added into a 4L polymerization tank, the temperature was controlled at 0°C and the mixture was stirred at high speed for 30 minutes, and then the temperature was raised to 30°C and the reaction was continued for 15 hours to obtain the precursor PHA-PPTA polymer solution.
[0057] Step 2:
[0058] The precursor PHA-PPTA polymer solution obtained in step 1 is added with triethylamine to neutralize the hydrochloric acid in the solution system, filtered, diluted to a dilution with a mass concentration of 2%, mixed and degassed (after mixing in a polymerization kettle, the solution is slowly stirred and degassed at 50°C for 5 hours under a vacuum degree of -0.08Mpa), and then the treated solution is injected into the stirred and temperature-controlled NMP precipitate, the stirring speed of which is 5000 rpm, and the injection conditions include: the temperature is 35°C; the volume ratio of the diluted precursor PHA-PPTA dilution solution to the precipitate is 1:15; under the action of high-speed stirring, it is rapidly dispersed into an ultra-thin flocculent PHA-PPTA precipitated fiber suspension with a dendritic structure; the suspension is filtered, washed (washed with desalted water), and dried (placed in a vacuum drying oven for drying, drying conditions: vacuum degree: -0.09Mpa, temperature: 120°C, time 3h), to obtain PHA-PPTA copolymerized precipitated fibers.
[0059] A method for preparing PBO-PPTA fibrids, wherein PHA-PPTA copolymerized fibrids are subjected to high-temperature cyclization to obtain PBO-PPTA fibrids with a high specific surface area, wherein the conditions for the thermal cyclization include: a vacuum degree of -0.09 Mpa, a temperature of 450°C, and a time of 15 minutes.
[0060] The PBO fibrillated pulp prepared by the above method has an average length of 2.1 mm and a specific surface area of 35 m 2 / g.
[0061] Example 4
[0062] A method for preparing PHA-PPTA fibrids comprises the following steps:
[0063] Step 1:
[0064] In a 2L polymerization tank, add 500ml of N-methylpyrrolidone, pass nitrogen, add 10.71g of 4,6-diaminoresorcinol hydrochloride, add 0.01g of antioxidant stannous chloride, stir and react for 30min, add 10.72g of terephthaloyl chloride, stir for 30min, add 0.15g of catalyst pyridine, control the temperature at 35℃ and stir and react for 10h to obtain prepolymer solution A.
[0065] In a 4L polymerization tank, add 2000ml of N-methylpyrrolidone, pass nitrogen, add 61.68g of lithium chloride as a dissolving salt, and completely dissolve it under stirring at 80°C. Then lower the system temperature to 5°C, add 21.75g of p-phenylenediamine, and after it is completely dissolved, add 30.11g of terephthaloyl chloride, control the temperature at 30°C, stir and react for 10 hours, and obtain a prepolymer solution B.
[0066] Then, the prepolymerization solution A and the prepolymerization solution B were added into a 5L polymerization tank, the temperature was controlled at 5°C and the mixture was stirred at high speed for 30 minutes, and then the temperature was raised to 80°C and the reaction was continued for 5 hours to obtain the precursor PHA-PPTA polymer solution.
[0067] Step 2:
[0068] The precursor PHA-PPTA polymer solution obtained in step 1 is added with diethylamine to neutralize the hydrochloric acid in the solution system, filtered, diluted to a dilution with a mass concentration of 5%, mixed and degassed (after mixing in a polymerization kettle, the solution is slowly stirred and degassed at 60°C for 5 hours under a vacuum degree of -0.08Mpa), and then the treated solution is injected into a stirred and temperature-controlled NMP-water-ethanol precipitate, the stirring speed of which is 1000 rpm, and the injection conditions include: the temperature is 60°C; the volume ratio of the diluted precursor PHA-PPTA dilution solution to the precipitate is 1:15; under the action of high-speed stirring, the solution is rapidly dispersed into an ultra-thin flocculent PHA-PPTA precipitated fiber suspension with a dendritic structure; the suspension is filtered, washed (washed with desalted water), and dried (placed in a vacuum drying oven for drying, the drying conditions are: vacuum degree: -0.09Mpa, temperature: 120°C, time 3h), to obtain PHA-PPTA copolymerized precipitated fibers.
[0069] A method for preparing PBO-PPTA fibrids, wherein PHA-PPTA copolymerized fibrids are subjected to high-temperature cyclization to obtain PBO-PPTA fibrids with a high specific surface area, wherein the conditions for the thermal cyclization include: a vacuum degree of -0.05 MPa, a temperature of 300°C, and a time of 40 minutes.
[0070] The PBO fibrillated pulp prepared by the above method has an average length of 1.5 mm and a specific surface area of 19 m 2 / g.
[0071] Example 5
[0072] A method for preparing PHA-PPTA fibrids comprises the following steps:
[0073] Step 1:
[0074] In a 1L polymerization tank, add 280ml of N,N-dimethylacetamide and dimethylformamide, pass nitrogen, add 60.00g of 4,6-diaminoresorcinol hydrochloride, add 0.06g of antioxidant stannous chloride, stir and react for 30min, add 61.74g of terephthaloyl chloride, stir for 30min, add catalyst isoquinoline and 3.60g of triethylamine, control the temperature at 0℃ and stir and react for 30h, to obtain prepolymer solution A.
[0075] In a 250ml polymerization tank, add 70ml of N,N-dimethylacetamide and dimethylformamide, pass nitrogen, add 5.60g of lithium chloride as a dissolving salt, and completely dissolve it under stirring at 80°C, then lower the system temperature to 5°C, add 7.62g of p-phenylenediamine, and after it is completely dissolved, add 9.72g of terephthaloyl chloride, control the temperature at 0°C and stir to react for 30h to obtain a prepolymer solution B.
[0076] Then, the prepolymerization solution A and the prepolymerization solution B were added into a 1L polymerization tank, the temperature was controlled at 0°C and the mixture was stirred at high speed for 30 minutes, and then the temperature was raised to 20°C and the reaction was continued for 20 hours to obtain the precursor PHA-PPTA polymer solution.
[0077] Step 2:
[0078] The precursor PHA-PPTA polymer solution obtained in step 1 is added with diethylamine to neutralize the hydrochloric acid in the solution system, filtered, diluted to a dilution with a mass concentration of 1%, mixed and degassed (after mixing in a polymerization kettle, the solution is slowly stirred and degassed at 60°C for 5 hours under a vacuum degree of -0.08Mpa), and then the treated solution is injected into a stirred and temperature-controlled DMAC-water-acetone precipitate, the stirring speed of which is 9000 rpm, and the injection conditions include: the temperature is 15°C; the volume ratio of the diluted precursor PHA-PPTA dilution solution to the precipitate is 1:15; under the action of high-speed stirring, the solution is rapidly dispersed into an ultra-thin flocculent PHA-PPTA precipitated fiber suspension with a dendritic structure; the suspension is filtered, washed (washed with desalted water), and dried (placed in a vacuum drying oven for drying, the drying conditions are: vacuum degree: -0.09Mpa, temperature: 120°C, time 3h), to obtain PHA-PPTA copolymerized precipitated fibers.
[0079] A method for preparing PBO-PPTA fibrids, wherein PHA-PPTA copolymerized fibrids are subjected to high-temperature cyclization to obtain PBO-PPTA fibrids with a high specific surface area, wherein the conditions for the thermal cyclization include: a vacuum degree of -0.07 Mpa, a temperature of 480°C, and a time of 5 minutes.
[0080] The PBO fibrillated pulp prepared by the above method has an average length of 0.9 mm and a specific surface area of 17 m 2 / g.
[0081] Comparative Example 1
[0082] The Chinese patent with publication number CN113882185A discloses a method for preparing PBO fibrillated pulp for preparing pulp. The prepared PBO fibrillated pulp has an average length of 1.2-2.5 mm and a specific surface area of 30-40 m 2 / g.
[0083] Comparative Example 2
[0084] The Chinese patent publication number CN109321998A discloses a method for preparing poly(p-phenylene terephthalamide) PPTA fibrils. The prepared poly(p-phenylene terephthalamide) PPTA fibrils have a larger specific surface area (20-40 m 2 / g) and morphology controllability (a strip-shaped solid material with a thickness of about 1-3um under a microscope) are more conducive to the wide application of poly(p-phenylene terephthalamide) precipitated fibers in other (papermaking) fields.
[0085] Comparative Example 3
[0086] The Chinese patent with publication number CN110184677A discloses a method for preparing PPTA-MPIA in-situ composite fibrils. The prepared PPTA-MPIA composite fibrils have good dispersibility in water, a beating degree of 25-35°SR, and a specific surface area of 6.2-7.8m 2 / g, the average fiber length is 0.6-0.9mm. In addition to comparing some specific surface areas, fiber lengths, and beating degrees, it is not very informative. Therefore, the applicant has done it in paper and indirectly explained the composite reinforcement effect by comparing the tensile index and tear index.
[0087] Comparative Example 4
[0088] A method for preparing PHA-PPTA fibrids comprises the following steps:
[0089] Step 1:
[0090] In a 2L polymerization tank, add 600 ml of N,N-dimethylacetamide, pass nitrogen, add 30.00 g of 4,6-diaminoresorcinol hydrochloride, add 0.03 g of antioxidant stannous chloride, stir and react for 30 min, add 30.87 g of terephthaloyl chloride, stir for 30 min, add 0.75 g of catalyst isoquinoline, control the temperature at 35 °C and stir and react for 18 h to obtain prepolymer solution A.
[0091] In a 2L polymerization tank, add 600ml of N,N-dimethylacetamide, pass nitrogen, add 30.00g of lithium chloride as a dissolving salt, and completely dissolve it under stirring at 80°C. Then lower the system temperature to 15°C, add 15.22g of p-phenylenediamine, and after it is completely dissolved, add 24.74g of terephthaloyl chloride, control the temperature at 15°C, stir and react for 12h, and obtain prepolymer solution B.
[0092] Then, the prepolymerization solution A and the prepolymerization solution B were added into a 4L polymerization tank, the temperature was controlled at 5°C and the mixture was stirred at high speed for 30 minutes, and then the temperature was raised to 40°C to continue the reaction for 15 hours, thereby obtaining the precursor PHA-PPTA polymer solution.
[0093] Step 2:
[0094] The precursor PHA-PPTA polymer solution obtained in step 1 is added with diethylamine to neutralize the hydrochloric acid in the solution system, filtered, diluted to a diluent with a mass concentration of 1%, mixed and degassed (after mixing in a polymerization kettle, the solution is slowly stirred and degassed at 60°C for 5 hours under a vacuum degree of -0.08Mpa), and then the treated solution is injected into the stirred and temperature-controlled DMAC precipitate, the stirring speed of which is 5000 rpm, and the injection conditions include: the temperature is 20°C; the volume ratio of the diluted precursor PHA-PPTA dilution solution to the precipitate is 1:15; under the action of high-speed stirring, the solution is rapidly dispersed into an ultra-thin flocculent PHA-PPTA precipitated fiber suspension with a dendritic structure; the suspension is filtered, washed (washed with desalted water), and dried (placed in a vacuum drying oven for drying, the drying conditions are: vacuum degree: -0.09Mpa, temperature: 120°C, time 3h), to obtain PHA-PPTA copolymerized precipitated fibers.
[0095] A method for preparing PBO-PPTA fibrids, wherein PHA-PPTA copolymerized fibrids are subjected to high-temperature cyclization to obtain PBO-PPTA fibrids with a high specific surface area, wherein the conditions for the thermal cyclization include: a vacuum degree of -0.09 Mpa, a temperature of 450°C, and a time of 10 minutes.
[0096] The PBO fibrillated pulp prepared by the above method has an average length of 1.1 mm and a specific surface area of 23 m 2 / g.
[0097] Comparative Example 5
[0098] A method for preparing PHA-PPTA fibrids comprises the following steps:
[0099] Step 1:
[0100] In a 2L polymerization tank, add 600 ml of N,N-dimethylacetamide, pass nitrogen, add 30.00 g of 4,6-diaminoresorcinol hydrochloride, add 0.03 g of antioxidant stannous chloride, stir and react for 30 min, add 30.87 g of terephthaloyl chloride, stir for 30 min, add 0.75 g of catalyst isoquinoline, control the temperature at 0°C and stir and react for 30 h to obtain prepolymer solution A.
[0101] In a 2L polymerization tank, add 600ml of N,N-dimethylacetamide, pass nitrogen, add 20.00g of lithium chloride as a dissolving salt, and completely dissolve it under stirring at 80°C. Then lower the system temperature to 0°C, add 10.15g of p-phenylenediamine, and after it is completely dissolved, add 15.38g of terephthaloyl chloride, control the temperature at 0°C and stir to react for 28h to obtain a prepolymer solution B.
[0102] Then, the prepolymerization solution A and the prepolymerization solution B were added into a 4L polymerization tank, the temperature was controlled at 0°C and the mixture was stirred at high speed for 30 minutes, and then the temperature was raised to 15°C and the reaction was continued for 20 hours to obtain the precursor PHA-PPTA polymer solution.
[0103] Step 2:
[0104] The precursor PHA-PPTA polymer solution obtained in step 1 is added with diethylamine to neutralize the hydrochloric acid in the solution system, filtered, diluted to a diluent with a mass concentration of 1%, mixed and degassed (after mixing in a polymerization kettle, the solution is slowly stirred and degassed at 60°C for 5 hours under a vacuum degree of -0.08Mpa), and then the treated solution is injected into the stirred and temperature-controlled DMAC precipitate, the stirring speed of which is 5000 rpm, and the injection conditions include: the temperature is 20°C; the volume ratio of the diluted precursor PHA-PPTA dilution solution to the precipitate is 1:15; under the action of high-speed stirring, the solution is rapidly dispersed into an ultra-thin flocculent PHA-PPTA precipitated fiber suspension with a dendritic structure; the suspension is filtered, washed (washed with desalted water), and dried (placed in a vacuum drying oven for drying, the drying conditions are: vacuum degree: -0.09Mpa, temperature: 120°C, time 3h), to obtain PHA-PPTA copolymerized precipitated fibers.
[0105] A method for preparing PBO-PPTA fibrids, wherein PHA-PPTA copolymerized fibrids are subjected to high-temperature cyclization to obtain PBO-PPTA fibrids with a high specific surface area, wherein the conditions for the thermal cyclization include: a vacuum degree of -0.09 Mpa, a temperature of 450°C, and a time of 10 minutes.
[0106] The PBO fibrillated pulp prepared by the above method has an average length of 1.0 mm and a specific surface area of 19 m 2 / g.
[0107] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing PHA-PPTA copolymerized fibrils, characterized in that: The following steps are involved: Step 1: Prepare the precursor PHA-PPTA polymer solution: Using 4,6-diaminoresorcinol hydrochloride as the first reaction monomer and terephthaloyl chloride as the second reaction monomer, under nitrogen protection, adding a certain amount of aprotic polar solvent, adding an antioxidant stannous chloride, adding the first reaction monomer 4,6-diaminoresorcinol hydrochloride, adding a catalyst and the second reaction monomer terephthaloyl chloride at one time under stirring, controlling the temperature at 0-35° C. to react for 10-30 hours, thereby preparing a prepolymer solution A; With p-phenylenediamine as the third reaction monomer and terephthaloyl chloride as the fourth reaction monomer, under nitrogen protection, add a certain amount of aprotic polar solvent, add dissolving salt lithium chloride, add the third reaction monomer p-phenylenediamine, stir to dissolve, add the fourth reaction monomer terephthaloyl chloride at one time under stirring, control the temperature at 0-30°C to react for 10-30h, and obtain a prepolymer solution B; Add prepolymer solution A and prepolymer solution B into a polymerization kettle, control the temperature at 0-5°C, stir and mix for 30 minutes, then raise the temperature to 20-80°C and continue the reaction for 5-20 hours to obtain a precursor PHA-PPTA polymer solution; Step 2: The precursor PHA-PPTA polymer solution obtained in step 1 is neutralized with an organic amine, diluted to a mass concentration of 1-5%, mixed and degassed, and then the treated solution is injected into a stirred and temperature-controlled precipitate, and under stirring, it is quickly dispersed into an ultra-thin flocculent PHA-PPTA precipitated fiber suspension with a dendritic structure; The suspension is filtered, washed and dried to obtain PHA-PPTA copolymerized fibrils.
2. The method for preparing a PHA-PPTA copolymerized fibrid according to claim 1, characterized in that: The non-protonic polar solvent in step 1 is one or more of N-methylpyrrolidone, dimethylformamide, and N,N-dimethylacetamide. In preparing prepolymer solution A, the molar concentration of the first reaction monomer 4,6-diaminoresorcinol hydrochloride is 0.1 mol / L to 1 mol / L; in preparing prepolymer solution B, the molar concentration of the third reaction monomer p-phenylenediamine is 0.1 mol / L to 1 mol / L.
3. The method for preparing a PHA-PPTA copolymerized fibrid according to claim 2, characterized in that: In the step 1, the total molar amount of the first reaction monomer and the third reaction monomer added and the total molar amount of the second reaction monomer and the fourth reaction monomer added are in a ratio of 1:0.8-1.0, wherein the molar ratio of the first reaction monomer to the third reaction monomer is 8-2:2-8.
4. The method for preparing a PHA-PPTA copolymerized fibrid according to claim 3, characterized in that: When preparing the prepolymer solution A in step 1, the antioxidant stannous chloride is added in an amount of 0.1-3 wt % of 4,6-diaminoresorcinol hydrochloride; When preparing the prepolymer solution B, the mass of the dissolution-aiding salt lithium chloride added is 3-8% of the aprotic polar solvent.
5. The method for preparing a PHA-PPTA copolymerized fibrid according to claim 4, characterized in that: In the step 1, the catalyst is at least one of pyridine, triethylamine or isoquinoline, and the mass of the catalyst is 0.5-6 wt % of the mass of 4,6-diaminoresorcinol hydrochloride.
6. The method for preparing a PHA-PPTA copolymerized fibrid according to claim 5, characterized in that: The stirring speed of the stirring in the step 2 is 1000-9000 rpm, and the injection conditions include: the temperature is 15-60°C.
7. The method for preparing a PHA-PPTA copolymerized fibrid according to claim 6, characterized in that: The precipitate in step 2 is at least one or more of DMAC, NMP, water, methanol, ethanol and acetone.
8. The method for preparing a PHA-PPTA copolymerized fibrid according to claim 7, characterized in that: The volume ratio of the diluted precursor PHA-PPTA dilution liquid to the precipitate liquid in step 2 is 1:
15.
9. A method for preparing PBO-PPTA fibrids, characterized in that: The PHA-PPTA copolymer fibrid according to any one of claims 1 to 8 is subjected to high temperature thermal cyclization under high vacuum conditions to prepare PBO-PPTA fibrid.
10. The method for preparing PBO-PPTA fibrid according to claim 9, characterized in that: The conditions of the thermal cyclization include: vacuum condition of -0.05Mpa~-0.09MPa, temperature of 300-480°C, and time of 5-40min.
Citation Information
Patent Citations
Method for preparing poly(p-phenylene terephthalamide) PPTA fibrid
CN109321998A
Preparation method of PPTA-MPIA in-situ composite fibrid
CN110184677A
Preparation method of PBO fibrid used for preparing pulp
CN113882185A
Synthetic fiber paper for highly heat-resistant circuit board with negative thermal expansion coefficient and preparation method and application
CN104674594A
Wholly-aromatic polymer fiber with high compound property and preparing method thereof
CN105821655A